ANALISIS KELAYAKAN DANAU TAJWID (KAJUID) SEBAGAI OBJEK WISATA DI KECAMATAN LANGGAM KABUPATEN PELALAWAN - Afdia Yulesti; Hendro Ekwarso; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to know the feasibility level knowing Tajwid Lake (Kajuid) as the sights seen from the aspect of natural attractions, accessibility and infrastructure and knowing the behavior of visitors to Lake Tajwid (Kajuid) viewed from the tourists who visit. This research uses techniques of accidental sampling and sample 44 people elected by the method of data collection is done is a technique question form/questionnaire. Analysis of the method used is descriptive quantitative methods. The analysis of the data by using the score and percentage. From the results obtained that the indicators of natural attractions on aspects of assessment levels are in class II IE support with percentage 17,76%. Assessment on the level of accessibility is the grade II with a percentage of 18,34%. Indicators and infrastructure with percentage 31.81% class III that is less supportive. Visitor behavior as seen from tourists visiting the Lake Tajwid (Kajuid) mostly to vacationers (90,09%) with the number of visits is more than 2 times (54,54%) and within a day and does not stay (97.72%) and visitors buying souvenirs in the form of agriculture and fisheries (68,18%) with the required fee to the tour range between Rp 15.000 – Rp 34.999 per person.Keywords : Feasibility, Lake Tajwid (Kajuid), Attractions, Scoring